2023
DOI: 10.1038/s41598-023-39306-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extruded injector nozzle on fuel mixing and mass diffusion of multi fuel jets in the supersonic cross flow: computational study

Abstract: The efficient injection system has a great role on the overall enactment of air breathing propulsion systems at supersonic flow. In this work, the usage of extruded multi-injectors in the fuel distribution and mixing through the combustor is fully investigated. The usage of the extruded nozzles considerably intensifies the formation of the vortices nearby the injectors and this research has tried to visualize the role of these vortices on the diffusion of the fuel jet through the combustor of the scramjet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The modeling of fuel mixing of the transverse jet at the high-velocity free stream at the combustion chamber is mainly done via solving Reynolds-averaged Navier–Stokes equation (RANS) equations 37 , 38 . The supersonic inflow encounters the fuel jet and the cross-jet flow creates the shock wave near the jet consequently, the energy equation is also coupled for the existence of the shock wave.…”
Section: Governing Equations and Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling of fuel mixing of the transverse jet at the high-velocity free stream at the combustion chamber is mainly done via solving Reynolds-averaged Navier–Stokes equation (RANS) equations 37 , 38 . The supersonic inflow encounters the fuel jet and the cross-jet flow creates the shock wave near the jet consequently, the energy equation is also coupled for the existence of the shock wave.…”
Section: Governing Equations and Numerical Methodologymentioning
confidence: 99%
“…By employing advanced numerical modeling techniques, engineers can analyze the fluid dynamics inside combustion chambers with varying injector sizes, providing insights into flow patterns, fuel dispersion, and combustion characteristics. Such simulations enable the optimization of injector dimensions to achieve the desired fuel–air mixing quality 37 , 38 . Abdollahi et al 37 investigated influence of extruded injector nozzle on fuel mixing and mass diffusion of multi fuel jets in the supersonic cross flow via computational study.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of high-speed air stream with compressibility effects is mainly done via solving RANS equations for continuum domain 37 40 . The shock wave formation is inherently happened in our model and consequently, the energy equation must be considered in our modeling 41 , 42 .…”
Section: Governing Equations and Numerical Methodologymentioning
confidence: 99%
“…There are many studies on the use of geometrically assisted secondary injection. In 2023, Abdollahi et al [95] conducted a numerical simulation study on the application of squeeze-type nozzles in fuel distribution and combustion mixing processes in supersonic combustion chambers. The study showed that the application of squeeze-type multi-nozzles significantly enhanced the formation of vortices near the injector in the combustion chamber.…”
Section: Fuel Mixing In a Scramjet Enginementioning
confidence: 99%